The applications of big data in the insurance industry: A bibliometric and systematic review of relevant literature - Nejla Ellili; Haitham Nobanee; Lama Alsaiari; Hiba Shanti; Bettylucille Hillebrand; Nadeen Hassanain; Leen Elfout (Journal of Finance and Data Science, 2023)
The insurance industry has changed rapidly over the last few decades. One factor in this change is the continuous growth of massive amounts of data that need to be processed properly to be optimally utilized. This has led to a strong wave of advanced processing technologies that can systematically manage big datasets, such as machine learning and artificial intelligence. This study analyzes the current state of research on big data and insurance. Bibliometric analysis and a systematic review were conducted to analyze the patterns and trends of the subject area, with the main focus on citations as a key measurement unit. This analysis is important to fill the existing gap in the examined area because no other bibliometric analysis has been conducted previously on the same subject; it will also help in establishing a scientific background for future research. The research findings verify that the United States is the most popular and cited country in the research area of big data and insurance at both the single authorship and co-authorship levels. Finally, the major impact of the relationship between big data and the insurance sector was marked by human-related aspects.